Pengaruh Komisaris Independenden dan Pengungkapan ESG terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Moderasi - Sri Ayem; Maksimilianus Bobat (Yayasan Literasi Ilmiah Indonesia, 2025)
Purpose: This study aims to determine the effect of independent commissioners and ESG disclosure on company value, with profitability as a moderating variable. Method: This study uses a quantitative method, namely presenting research results in numerical form which are then explained and interpreted descriptively, to test the hypothesis. The subjects of this study were manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the industrial goods sector. The sample of this study was 32 companies during the observation period 2021-2023, so that 96 observation units were obtained using purposive sampling. Finding: The test results show that the variables of independent commissioners and ESG disclosure have an effect on firm value. However, profitability is unable to moderate the effect of independent commissioners and ESG disclosure on firm value. Novelty: This study combines independent commissioners and ESG disclosure as two main aspects of corporate governance and sustainability, which are analyzed simultaneously against firm value. This combination has not been widely discussed simultaneously in the context of Indonesian manufacturing companies.